A recent HIV diagnosis is associated with non-completion of Isoniazid Preventive Therapy in an HIV-infected cohort in Cape Town. - Tolu Oni; Relebohile Tsekela; Bekekile Kwaza; Lulama Manjezi; Nonzwakazi Bangani; Katalin A Wilkinson; David Coetzee; Robert J Wilkinson (PLoS ONE)
Introduction Despite high rates of successful treatment TB incidence in South Africa remains high, suggesting ongoing transmission and a large reservoir of latently infected persons. Isoniazid preventive therapy (IPT) is recommended as preventive therapy in HIV-infected persons. However, implementation has been slow, impeded by barriers and challenges including the fear of non-adherence. Objective and methods The aim was to evaluate predictors of IPT non-completion. One hundred and sixty four antiretroviral therapy (ART)-naïve HIV-infected patients with tuberculin skin test ≥5 mm were recruited from Khayelitsha day hospital and followed up monthly. A questionnaire was used to collect demographic information. Results The overall completion rate was 69%. In multivariable analysis, there was a 29% decrease in risk of non-completion for every year after HIV diagnosis (OR 0.81; 95% C.I. 0.68-0.98). Self-reported alcohol drinkers (OR 4.05; 95% C.I. 1.89-9.06) also had a four-fold higher risk of non-completion, with a strong association between alcohol drinkers and smoking (χ(2) 27.08; p<0.001). Conclusion We identify patients with a recent HIV diagnosis, in addition to self-reported drinkers and smokers as being at higher risk of non-completion of IPT. The period of time since HIV diagnosis should therefore be taken into account when initiating IPT. Our results also suggest that smokers and alcohol drinkers should be identified and targeted for adherence interventions when implementing IPT on a wider scale.